Analysis of Barrier Factors for Collaboration in Handling Used Cell Phones for Second-hand Market Actors to Implement e-waste Management - Siti Mahsanah Budijati; I Nyoman Pujawan; Hayati Mukti Asih (Salehan Institute of Higher Education, 2023)
Waste management is an activity to manage residues, by-products, and used items. Handling used cell phones is one form of waste management activity. In developing countries, used cell phones are mostly handled by informal actors, where second-hand market actors for cell phones act as collection points. Some of these activities often affect the environment and the actors' health due to a lack of adequate technology. Hence, a collaboration between informal and formal actors is necessary to handle the used cell phones and reduce the adverse effects. However, several obstacles faced by informal actors can hinder such collaboration. This study explores the inhibiting factors for the collaboration between the informal and formal actors in handling used cell phones. The respondents were 424 informal actors in five areas of the Special Region of Yogyakarta (DIY Province), Indonesia. The results showed that the unavailability of infrastructure and insufficient organization significantly hindered collaboration in the Yogyakarta municipal area. As for the areas of Gunungkidul, Bantul, Kulonprogo, and Sleman regions, there were no significant factors hindering the collaboration. The results of this study can contribute for stakeholders’ consideration related to e-waste handling, primarily used cell phones in Indonesia; thus, the management of used cell phones is safe for the environment and provide economic benefits for the informal actors. Doi: 10.28991/CEJ-2023-09-03-011 Full Text: PDF